Perspective of wireless sensor networks towards Environment: Gaps and Challenges. Issue 1 (August 2021) - Rajshree; Passi, Abhiruchi; Soni, M.K.
Abstract: Wireless sensor networks have a huge number of applications in the environment for sensing and broadcasting the information at very low cost. Wireless sensor networks are composed of a large number of nodes which are deployed in close proximity to the phenomenon to be monitored. The wireless sensor network is comprised of computing, communication and sensing elements which gives the opportunity to the administrator to an object, sense and an instrument in the events in a specified environment. They are popular due to unique and advance property of wireless sensor but they have fundamental problems like limited battery life, overhearing, coverage area, node deployment, blindness and much more This paper will address various issues related to wireless sensor networks in environmental field The various challenges comprehended in wireless sensor network while constructing the deployment algorithms and communication protocols are coverage area, efficient data gathering, sensor lifetime and overhearing.